Persona Perception Scale: Development and Exploratory Validation of an Instrument for Evaluating Individuals' Perceptions of Personas. Issue 141 (September 2020) - Salminen, Joni; Santos, Joao M.; Kwak, Haewoon; An, Jisun; Jung, Soon-gyo; Jansen, Bernard J.
Abstract : We develop Persona Perception Scale (PPS), which is a survey instrument for evaluating how individuals perceive personas. The scale is based on relevant literature from social psychology, persona studies, and human-computer-interaction domains. We validate the scale with 412 survey respondents and find that the constructs and items of the scale perform satisfactorily for scale deployment into wider use of both researchers and practitioners. Using the PPS, researchers can e.g. investigate persona users' perceived credibility of the persona and their willingness to use it. Practitioners can use the PPS to understand how the personas they developed are perceived by persona users. Because perceptions are associated with adoption of personas, PPS can be used for improving the chances of persona adoption in a wide range of professional contexts. Abstract: Although used in many domains, the evaluation of personas is difficult due to the lack of validated measurement instruments. To tackle this challenge, we propose the Persona Perception Scale (PPS), a survey instrument for evaluating how individuals perceive personas. We develop the scale by reviewing relevant literature from social psychology, persona studies, and Human-Computer Interaction to find relevant constructs and items for measuring persona perceptions. Following initial pilot testing, we conduct an exploratory validation of the scale with 412 respondents and find that the constructs and items of the scale perform satisfactorily for deployment. The research has implications for both academic researchers and persona developers. Using the PPS, researchers and designers can evaluate how different persona designs affect individual perceptions of personas, for example persona users' (e.g., designers, marketers, software developers) perceived credibility of the persona and their willingness to use it. Because persona perceptions are associated with persona acceptance and adoption, using a perceptual measurement instrument can improve the chances of persona adoption and use in real organizations.